Konkurencyjność uzdrowisk słowackich na rynku usług uzdrowiskowych Europy - Gúčik, Marian (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The competitiveness of Slovak balneology in the European market refers to its medical nature id development of new health tourism products, which grows thanks to raising health awareness and purposeful prophylaxis. Besides it is necessary to invest in modernization of balneotherapy facilities, crease of accommodation standards and improvement of free-time activities in spas. To assure and improve quality of their services, spas should implement quality systems and get certificate of quality based on European norms ISO 9001:2001. Spas have to change their approach in terms of commercialisation of their products and public relations, including external and internal public. A major factor of balneology development is human resources development. Therefore it is necessary to improve communication and intercultural skills of employees. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 140-152